Coherent backscattering cone shape depends on the beam size - Bi, Renzhe (2013)
Coherent backscattering (CBS) is a beautiful physical phenomenon that takes place in a highly scattering medium, which has potential application in noninvasive optical property measurement. The current model that explains the CBS cone shape, however, assumes the incoming beam diameter is infinitely large compared to the transport length. In this paper, we evaluate the effect of a finite scalar light illumination area on the CBS cone, both theoretically and experimentally. The quantitative relationship between laser beam size and the CBS cone shape is established by using two different finite beam models (uniform top hat and Gaussian distribution). A series of experimental data with varying beam diameters is obtained for comparison with the theory. Our study shows the CBS cone shape begins to show distortion when beam size becomes submillimeter, and this effect should not be ignored in general. In biological tissue where a normal large beam CBS cone is too narrow for detection, this small beam CBS may be more advantageous for more accurate and higher resolution tissue characterization.